Sesquiterpene lactones from Artemisia vulgaris L. as potential NO inhibitors in LPS-induced RAW264.7 macrophage cells - Xiang-Yu Chen; Xiang-Yu Chen; Xiang-Yu Chen; Xiang-Yu Chen; Tao Liu; Tao Liu; Tao Liu; Tao Liu; Yu-Ze Hu; Tian-Tian Qiao; Tian-Tian Qiao; Tian-Tian Qiao; et al. (Frontiers in Chemistry, 2022)
Twelve new guaianolide sesquiterpene lactones (1–12), along with ten known analogs (13–22) were isolated from an EtOH extract of the dried aerial parts of Artemisia vulgaris L. The new structures were elucidated via abundant spectroscopic data analyses (HRESIMS, IR, 1D, and 2D NMR), and the absolute configurations of these compounds were determined by X-ray crystallography and ECD calculations. The compounds (1−22) were identified as guaiane-type sesquiterpenes with characteristic α-methylene-γ-lactone and α,β-unsaturated carbonyl moieties. All compounds were tested for their inhibitory activity against NO production in lipopolysaccharide-stimulated RAW264.7 macrophages. The isolated sesquiterpenoids dose-dependently exhibited an NO production inhibitory activity by inhibiting the expression of inducible NO oxidase (iNOS) and cyclooxygenase-2 (COX-2) with IC50 values ranging from 1.0 to 3.6 μM. The inhibitory effect on the NO production of the compounds (1–4 and 6–22) is better than that of the positive control (dexamethasone). The different substitutions of compounds on C-8 influence anti-inflammatory effects, as evidenced by the in silico analysis of related binding interactions of new compounds (1–12) with iNOS.